Folding architecture : spatial, structural and organizational diagrams. - Vyzoviti, Sophia, ....- (Amsterdam : Bis, 2006)
Sofia Vyzoviti explores the issue of paper folding as a spatial, structural and organizational diagram. In a foremost visual way the volume shows many folding techniques and folding algorithms which can be used in the design process.
Keywords: Verpakkingen; Vouwconstructies